Pengaruh Motivasi dan Lingkungan Kerja terhadap Turnover Intention Pada Generasi Milenial - Stefanya, Yemima; Winarto, Jacinta (SAFE-Network, 2024)
This research aims to analyze the influence of work motivation and work environment on turnover intention at Property Company X in Bandung City using a quantitative approach. Data collection was carried out by distributing questionnaires to 40 employees. The results of this research are that both motivation and the work environment influence turnover intention. Motivation and the work environment also simultaneously influence turnover intention by 89.7%. There is an influence of work motivation on turnover intention in a negative direction. There is an influence between the work environment on turnover intention in a negative direction. Motivation and the work environment both simultaneously have an influence on the turnover intention of Property Company X employees. Property Company With increased motivation, employees will feel more engaged and satisfied, thereby reducing their likelihood of leaving the company. Property Company X can ensure that the work environment provided to employees is conducive and supportive. The company must have a pleasant working atmosphere, as well as support from the company. Comfortable working area conditions not only increase employee satisfaction but also encourage them to stay in the long term. Property Company X also needs to set clear and measurable goals that are in line with employees' personal aspirations. By setting specific and relevant goals, employees will feel more committed and motivated to achieve them. Apart from that, companies can also implement a team assessment system to increase accuracy and objectivity in performance appraisals.